GaPN/GaP nanowire-polymer matrix: photoluminescence study. (December 2020) - Koval, O Yu; Fedorov, V V; Bolshakov, A D; Neplokh, V V; Strom, I V; Serov, A Yu; Mukhin, I S
Abstract: This study is devoted to the investigation of the optical properties and composition of GaPN/GaP nanowire heterostructure. Nanowire arrays were grown on Si substrate (111) by the plasma-assisted molecular beam epitaxy. Polydimethylsiloxane membrane encapsulation was used to obtain the free-standing NW arrays. The morphology of GaPN/GaP NW was investigated with scanning electron microscopy. The optical properties of the GaPN nanowire arrays were determined at the He temperature (5K) with photoluminescence spectroscopy. Analysis of photoluminescence response allowed us to conclude that the incorporation of nitrogen atoms during the growth occurs both in the nanowires and in the parasitic islands with different content. Direct bandgap-like behaviour of the GaPN/GaP nanowires demonstrates the potential of nanowire-polymer matrix practical application in future optoelectronic devices.